2017
DOI: 10.21767/1791-809x.1000469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Utilization of Emergency Contraception among Unmarried Women of Reproductive Age in Adama, Ethiopia

Abstract: Background: Knowledge about methods of emergency contraception could reduce the level of unwanted pregnancy and unsafe abortion. Particularly, utilization of emergency contraception among unmarried women have beneficiary health outcome as it adds choice for helping sexually active unmarried women to avoid unintended pregnancy and its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…Similarly study conducted among Adama University revealed that 27.2% of the universities female students have good knowledge of emergency contraception. [15] And another study on emergency contraception among Haramaya university female students showed that twenty five percent the respondents had good knowledge of the contraception [17]. However, study conducted in Jimma University among the university students (graduating) indicated that 41.9% of study participants have awareness about emergency contraception [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly study conducted among Adama University revealed that 27.2% of the universities female students have good knowledge of emergency contraception. [15] And another study on emergency contraception among Haramaya university female students showed that twenty five percent the respondents had good knowledge of the contraception [17]. However, study conducted in Jimma University among the university students (graduating) indicated that 41.9% of study participants have awareness about emergency contraception [16].…”
Section: Discussionmentioning
confidence: 99%
“…Study done among Adama university female students showed that 27.2% and 62.9% students had good and favorable attitude respectively. Among these students the study found 4.7% utilized emergency contraception [15]. Study done among Jimma university graduating female students revealed that 41.9% of the participants aware of emergency contraception.…”
Section: Introductionmentioning
confidence: 91%
“…A study at Debre Markos University showed SRH/VCT service utilization was 58.5% among students [22]. Previous studies showed that VCT/SRH discussions with health care providers [22], information on health related services [19,21], age, educational status, and occupation were some of the factors associated with sexual and reproductive health service utilization among young students [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, adolescents and young people aged 10 to 24 years comprise about 30% of the population [10]. These people are disadvantaged in terms of having access to sexual and reproductive health information and services [10][11][12][13]. Gender inequality, sexual coercion, early sexual debut, unwanted/ unplanned pregnancy, adolescent pregnancy, abortion, sexually transmitted infections, and HIV/AIDS are the major youth sexual and reproductive problems in Ethiopia [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation